Grass carp (Ctenopharyngodon idella) ATF6 (activating transcription factor 6) modulates the transcriptional level of GRP78 and GRP94 in CIK cells. (May 2016) - Wang, Xiangqin; Zhang, Tao; Mao, Huiling; Mi, Yichuan; Zhong, Bin; Wei, Lili; Liu, Xiancheng; Hu, Chengyu
Abstract: ATF transcription factors are stress proteins containing alkaline area-leucine zipper and play an important role in endoplasmic reticulum stress. ATF6 is a protective protein which regulates the adaptation of cells to ER stress by modulating the transcription of UPR (Unfolded Protein Response) target genes, including GRP78 and GRP94 . In the present study, a grass carp ( Ctenopharyngodon idella ) ATF6 full-length cDNA (named CiATF6, KT279356) has been cloned and identified. CiATF6 is 4176 bp in length, comprising 159 nucleotides of 5′-untranslated sequence, a 1947 nucleotides open reading frame and 2170 nucleotides of 3′-untranslated sequences. The largest open reading frame of CiATF6 translates into 648 aa with a typical DNA binding domain (BRLZ domain) and shares significant homology to the known ATF6 counterparts. Phylogenetic reconstruction confirmed its closer evolutionary relationship with other fish counterparts, especially with Zebrafish ATF6. RT-PCR showed that CiATF6 was ubiquitously expressed and significantly up-regulated after stimulation with thermal stress in all tested grass carp tissues. In order to know more about the role of Ci ATF6 in ER stress, recombinant Ci ATF6N with His-tag was over-expressed in Rosetta Escherichia coli, and the expressed protein was purified by affinity chromatography with Ni-NTA His-Bind Resin. In vitro, gel mobility shift assays were employed to analyze the interaction of Ci ATF6 protein with the promoters of grass carp GRP78 and GRP94, respectively. The result has shown that CiATF6 could bind to these promoters with high affinity by means of its BRLZ mainly. To further study the transcriptional regulatory mechanism of Ci ATF6, Dual-luciferase reporter assays were applied. Recombinant plasmids of pGL3- GRP78P and pGL3- CiGRP94P were constructed and transiently co-transfected with pcDNA3.1- Ci ATF6 (pcDN3.1- Ci ATF6-nBRLZ, respectively) into C. idella kidney (CIK) cells. The result has shown that Ci ATF6 could activate CiGRP78 and CiGRP94 promoters. Highlights: The full-length cDNA of grass carp ATF6 was cloned and identified. CiATF6 was significantly up-regulated after stimulation with thermal stress. In vitro, Ci ATF6 had high affinity with CiGRP78 and CiGRP94 promoters. Ci ATF6 played a positive role in CiGRP78 and GRP94 transcription in CIK cells.